Penanaman Pola Pikir Kritis Berwawasan Eco-Pesantren Reduce Reuse dan Recycle di Pondok Modern Tazakka Batang - Hidayat, Ferry; Irianti, Danika Rahma; Restu, Pandu Wiguna; Sujiwa, Krisna; Aris Munandar; Achmad Munjid; Amin Basuki (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2022)
One of the Tri Dharma of College institutions is a form of community service. This program aims to provide education and hands-on practice regarding environmental management and procedures for managing waste properly and correctly to fellow students at Pondok Modern Tazakka in Batang district, Central Java. This community service is carried out using a Service-Learning approach. Robert Sigmon (1979), described service-learning as an experiential educational strategy based on “reciprocal learning”. The target of this activity is the students at Pondok Modern Tazakka with a total of 77 people with the result’s hope that they can understand how to manage waste properly, especially in the living environment so that it would not create a further environmental problem. This activity uses the form of seminar and direct practice in the form of making mind mapping about their creative ideas on how to manage waste, this activity runs smoothly and it is very visible through the enthusiasm of the students engaged in each of the agendas. The results of this activity are hoped that the students can directly practice the knowledge gained from educational activities on waste management and the environment. ==== Salah satu Tri Dharma Perguruan Tinggi adalah adanya kegiatan pengabdian masyarakat. Program ini bertujuan untuk memberikan edukasi dan praktik langsung mengenai pengelolaan lingkungan dan tata cara mengelola sampah yang baik dan benar kepada para santriwan di Pondok Modern Tazakka di Kabupaten Batang, Jawa Tengah. Kegiatan pengabdian ini dilaksanakan dengan pendekatan Service-Learning. Robert Sigmon (1979) menggambarkan Service-Learning sebagai strategi pendidikan pengalaman berdasarkan “Reciprocal Learning”. Sasaran kegiatan ini adalah sejumlah 77 orang santriwan Pondok Modern Tazakka, dengan harapan mereka bisa memahami cara mengelola sampah, khususnya di lingkungan tempat tinggal mereka, agar tidak menimbulkan masalah lingkungan. Kegiatan dilaksanakan melalui seminar dan praktik secara langsung, yang berupa pembuatan mind mapping tentang ide-ide kreatif cara pengelolaan sampah. Kegiatan ini berjalan dengan lancar dan sangat terlihat antusiasme dari para santriwan saat mengikuti setiap acara yang diselenggarakan oleh tim PkM. Melalui kegiatan edukasi ini diharapkan agar para santriwan dapat mempraktikkan ilmu yang diperoleh untuk pengelolaan sampah dan lingkungan.